Extracellular Vesicles as Drug Delivery System for the Treatment of Neurodegenerative Disorders: Optimization of the Cell Source. Issue 12 (16th August 2021) - Haney, Matthew J.; Zhao, Yuling; Fallon, John K.; Yue, Wang; Li, Samuel M.; Lentz, Emily E.; Erie, Dorothy; Smith, Philip C.; Batrakova, Elena V.
Abstract : Extracellular vesicles (EVs) represent a next generation drug delivery system that combines nanoparticle size with extraordinary ability to cross biological barriers, reduced immunogenicity, and low offsite toxicity profiles. A successful application of this natural way of delivering biological compounds requires deep understanding EVs intrinsic properties inherited from their parent cells. Herein, EVs released by cells of different origin, with respect to drug delivery to the brain for treatment of neurodegenerative disorders, are evaluated. The morphology, size, and zeta potential of EVs secreted by primary macrophages (mEVs), neurons (nEVs), and astrocytes (aEVs) are examined by nanoparticle tracking analysis (NTA), dynamic light scattering (DLS), cryogenic transmission electron microscopy (cryoTEM), and atomic force microscopy (AFM). Spherical nanoparticles with average size 110–130 nm and zeta potential around −20 mV are identified for all EVs types. mEVs show the highest levels of tetraspanins and integrins compared with nEVs and aEVs, suggesting superior adhesion and targeting to the inflamed tissues by mEVs. Strikingly, aEVs are preferentially taken up by neuronal cells in vitro, followed by mEVs and nEVs. Nevertheless, the brain accumulation levels of mEVs in a transgenic mouse model of Parkinson's disease are significantly higher than those of nEVs or aEVs. Therefore, mEVs are suggested as the most promising nanocarrier system for drug delivery to the brain. Abstract : Herein, a novel platform for brain delivery of therapeutics based on extracellular vesicles (EVs) for enabling a broader array for treatment of neurodegenerative disorders is developed. EVs may inherit at some extent properties of their parent cells. The data indicate that EVs released by inflammatory‐response cells, macrophages, are the most promising candidates for delivery of therapeutics to the inflamed brain.